PRE-SERVICE ENGLISH TEACHERS' READINESS TO DEVELOP DIGITALIZED AUTHENTIC MATERIALS WITH ISLAMIC VALUES - Al Azis, Edwin Nuvianto; Toyyibah, Toyyibah (Universitas Muhammadiyah Metro, 2023)
Pre-service English teachers still need to gain the competence to develop authentic materials with Islamic values, reflected by their low perceived readiness. To reveal their readiness, this study was conducted by using narrative inquiry. The data were gathered from the storytelling of pre-service English teachers pursuing master's degrees at IAIN Kediri. Participants in this study were one male and one female student with teaching experience. The data were analyzed by using thematic analysis. The data showed that the pre-service teachers believed the readiness to develop digitalized authentic materials with Islamic values could have been more optimal. It is because of the existing instructional materials provided by the government, their lack of confidence as new teachers, and their limited autonomous access to their classes as a new teacher. English textbooks provided by the government are only general English. So, it makes the teachers follow the materials instead of developing authentic materials with Islamic values that are fundamentally needed by students studying in Islamic institutions, such as modifying the materials from books to reflect Muslim activities. Therefore, the pre-service teachers must expose themselves to integrated materials books and digital materials with Islamic values.